The law as discourse. Theoretical and empirical scope of the legal norm as an ideological instrument in the construction of social representations - Albornoz Barra, Gonzalo (2018)
The Law, seen as discourse, allows reflection on its scope beyond the direct effects of its application on actors involved in judicialization processes. As discourse, and as an instrument loaded with legitimacy, the Law allows for the displacement of ideologies, while at the same time it becomes an instrument loaded with a false truthfulness for the construction of representations about the phenomena that regulates. These scopes of the Law, are give througth different forms of use, and through different platforms of consume that operate in the everyday life of the actors.